Rading Circle List for 2013 - Sharifah S., Wan Ahmad (Faculty of Social Sciences, 2013)
Reading Circle is a monthly event organised by the Faculty of Social Sciences. The objective is to inculcate the spirit of inquiry and intellectual discussion based on the readings of key texts in social sciences. Faculty members may suggest reading chapter to be brought for discussion. From time to time, prominent social scientists are also invited to share a reading on chosen topic.